Development of Augmented Reality-Based Learning Media in Early Childhood Learning - Sitti Rahmaniar Abubakar Rahmaniar; Salim (SEA-CECCEP, 2021)
The purpose of this research is: (1) to describe the characteristics of Augmented Reality-based learning media in early childhood learning in PAUD Kendari City institutions, (2) to find out the validity of Augmented Reality-based learning media to be used in early childhood learning in PAUD institutions in Kendari City, (3) how to effectively learn by using augmented reality-based learning media in PAUD institutions in Kendari City. This research is a research development or Research and Development (R & D) with a design model developed by Lee & Owens (2004) consisting of four stages assessment/analysis, design, development and implementation, evaluation. The results of this study showed that (1) media characteristics developed are (a) using Augmented Reality technology, (b) independent learning resources for children during the covid-19 pandemic, (c) have flashcards, (d) learning media developed are contextual; (2) The development of Augmented Reality-based learning media in early childhood learning has been valid after going through a little revision so that this media product is feasible to be used in learning in PAUD institutions in Kendari City. This is indicated by a validator rating average of 3.57 with a very valid category; (3) Development of Augmented Reality-based learning media is effective for use in the learning of children of age in PAUD institutions in Kendari City. This is shown by (a) the average percentage of child development of 87.62 is in the excellent category, (b) 85.71% of kindergarten teachers respond positively to augmented reality-based learning media, (c) there is an increase in aspects of child development after using Augmented Reality-based learning media. This is indicated by the significance value of the paired t-test being less than α = 0.05.